FOOD CHOICES: REGULAR CONSUMPTION OF ULTRA-PROCESSED AND HEALTHY FOODS BY EDUCATION WORKERS - Alves Santos, Gabriel Victor; Ferreira Santos Jesus, José Igor; Barbosa Costa, Milka; Oliveira Batista, Danyla Rafaela; Machado Félix, Amanda; Cristine Machado da Silva, Elaine; Carla Monteiro, Yasmin; Leal Cordeiro, Lavinia; Marçal Nogueira, Suelen; Rayanne e Silva, Priscilla; Noll, Matias (CIPEEX, 2025)
Introduction: The increased consumption of ultra-processed foods (UPFs) is concerning due to their negative health effects. In contrast, dietary patterns that prioritize fresh or minimally processed foods have been shown to be beneficial. Analyzing these practices is essential to developing effective public health care and prevention strategies. Objective: To associate regular consumption of ultra-processed/industrialized salty foods and healthy foods among employees of the Federal Network for Professional, Scientific, and Technological Education (RFEPCT). Method: Method: This cross-sectional epidemiological study employed a quantitative approach and was carried out in November 2022 after receiving approval from the Research Ethics Committee (protocol number 5,270,596). The sample consisted of 1,563 RFEPCT professionals, including teachers and TAE. Sociodemographic variables and the PeNSE questionnaire were analyzed. Consumption of sweets or healthy foods on ≥5 days per week was considered regular (CR), while consumption on ≤4 days per week was considered irregular (CI). The effect measure used was the prevalence ratio (PR) with 95% confidence intervals (CIs). Results: The CR of ultra-processed/industrialized salty foods was positively associated in the South (p = 0.019) and Southeast (p = 0.025) regions, teaching positions (p = 0.029), and master's degrees (p = 0.024); and negatively with the 48-60 age group (p = 0.008). We also observed a positive association with the CR of fresh fruits (p <0.001) and vegetables (p <0.010). We found no associations with female gender (p = 0.524), divorced/widowed marital status (p = 0.582), or rural area (p = 0.832). Conclusion: The findings suggest that the eating habits of RFEPCT professionals may be influenced by social conditions and occupational characteristics. Therefore, it is crucial to implement institutional initiatives that promote healthier food choices and contribute to health equity in the workplace.